Activity and safety of radiotherapy with anti-PD-1 drug therapy in patients with metastatic melanoma. (1st September 2016) - Liniker, E.; Menzies, A. M.; Kong, B. Y.; Cooper, A.; Ramanujam, S.; Lo, S.; Kefford, R. F.; Fogarty, G. B.; Guminski, A.; Wang, T. W.; Carlino, M. S.; Hong, A.; et al.
ABSTRACT: The anti-PD-1 antibodies nivolumab and pembrolizumab are active in metastatic melanoma; however, there is limited data on combining anti-PD-1 antibody and radiotherapy (RT). We sought to review clinical outcomes of patients receiving RT and anti-PD-1 therapy. All patients receiving anti-PD-1 antibody and RT for metastatic melanoma were identified. RT and systemic treatment, clinical outcome, and toxicity data were collected. Fifty-three patients were included; 35 patients received extracranial RT and/or intracranial stereotactic radiosurgery (SRS) and 21 received whole brain radiotherapy (WBRT) (three of whom also received SRS/extracranial RT). Patients treated with extracranial RT or SRS received treatment either sequentially (RT then anti-PD-1, n = 11), concurrently ( n = 16), or concurrent "salvage" treatment to lesions progressing on anti-PD-1 therapy ( n = 15). There was no excessive anti-PD-1 or RT toxicity observed in patients receiving extracranial RT. Of six patients receiving SRS, one patient developed grade 3 radiation necrosis. In 21 patients receiving WBRT, one patient developed Stevens–Johnson syndrome, one patient developed acute neurocognitive decline, and one patient developed significant cerebral edema in the setting of disease. Response in irradiated extracranial/intracranial SRS lesions was 44% for sequential treatment and 64% for concurrent treatment ( p =0.448). Likewise there was no significant difference between sequential or concurrent treatment in lesional response of non-irradiated lesions. For progressing lesions subsequently irradiated, response rate was 45%. RT and anti-PD-1 antibodies can be safely combined, with no detectable excess toxicity in extracranial sites. WBRT and anti-PD-1 therapy is well tolerated, although there are rare toxicities and the role of either anti-PD-1 or WBRT in the etiology of these is uncertain.